1982
DOI: 10.1007/bf01342191
|View full text |Cite
|
Sign up to set email alerts
|

Collective modes of one-dimensional lennard-jones systems

Abstract: The density fluctuations of one-dimensional Lennard-Jones systems are investigated by molecular dynamics simulation. The full Lennard-Jones potential is compared to the repulsive Lennard-Jones potential. It is found that the behavior of the density fluctuations at small wave vectors is determined by the repulsive portion of the potential. The variation of the fluctuations with density is explained. It is shown that these systems do not display hydrodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…In practice, as pointed out in Refs. [19,20], even in this case the interaction is limited to about 2-3 neighbours. Therefore, we do not expect that the results reported below will be significantly altered when taking into account the interaction among all pairs.…”
Section: The Modelmentioning
confidence: 88%
See 1 more Smart Citation
“…In practice, as pointed out in Refs. [19,20], even in this case the interaction is limited to about 2-3 neighbours. Therefore, we do not expect that the results reported below will be significantly altered when taking into account the interaction among all pairs.…”
Section: The Modelmentioning
confidence: 88%
“…Of particular relevance in what follows is the work of Bishop and collaborators [19,20]. At variance with our model, they considered the case in which the interaction is extended to all particle pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Early results seem to be rather inconclusive about whether it has a finite thermal conductivity or not [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional hydrodynamic theory predicts that a perturbation may induce a heat mode and a sound mode [2], hence the relaxation of a fluctuation may be understood as a combination of such two types of hydrodynamic modes. However, in recent decades, it has been found that the linearized hydrodynamic description may be invalid in low-dimension systems [3][4][5]. Therefore, it is necessary to investigate, by direct simulations, the particular properties of the hydrodynamic modes and show how they manifest themselves in different systems.…”
Section: Introductionmentioning
confidence: 99%